A Simulator For Degasification, Methane Emission Prediction, And Mine Ventilation - S. B. Patton (Society for Mining, Metallurgy & Exploration, 1992)
A computer model, which quantitatively utilizes the relationship between the interactive and dynamic processes of methane drainage, mining, and ventilation, is presented. The model includes simulation of the coalbed methane reservoir for prediction of gas-emission rates under the influence of degasification wells and longwall mining, ventilation network-generation, and ventilation simulation. As mining progresses step-wise through the coalbed-methane reservoir, the ventilation network is created and subsequently simulated, iteratively determining fan requirements to safely reduce methane concentrations. The model can be used to quantitatively study the effectiveness of methane degasification on the ventilation system in a longwall panel.